Raman Investigations of Metal Chalcogenide Thin Films (A Short Review) - Ho, Soon Min (Oriental Scientific Publishing, 2019)
Preparation and characterization of thin films have been reported by many researchers. Research of nanostructured thin films has recently received great attention due to their specific properties. The films obtained can be used for the development of optoelectronic, solar cells, laser devices and gas sensor. Several methods (X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, UV-Visible spectrophotometer, transmission microscopy and Fourier Transform Infrared spectroscopy) have been employed to study the materials in terms of structural, morphological, compositional, optical and electrical properties. In this short paper, Raman spectroscopy was used to characterize the properties of thin films. There are very clear advantages and disadvantages of this tool that need to be considered when using it. The obtained results highlight Raman spectra were used to confirm the purity of sample and the phase identification.